POLICY FORMULATION AGAINST BRIBERY IN THE PRIVATE SECTOR IN INDONESIAN CRIMINAL LAW REFORM - I Gusti Ayu Werdhiyani; I Ketut Rai Setiabudhi (Lafadz Jaya Publisher, 2023)
The purpose of this research is to analyze the regulation of bribery in the private sector in Indonesian positive law and future Indonesian criminal law formulation policies in terms of regulating bribery in the private sector. This research used normative legal research which departs from vacuum of norms with the type of approach used are statutory approach, analytical approach and legal concepts, comparative approach, and case approach. The results of the study show that basically Indonesia already has Act Number 11 of 1980, but it seems to be neglected or never been used. Although bribery in the private sector is non-mandatory, it is important for Indonesia to consider criminalizing bribery in the private sector, therefore it is necessary for legislators to form a criminal law policy by criminalizing bribery in the private sector as well as conducting comparative studies in several countries to address the gap, so the law enforcement can carry out law enforcement in accordance with the regulations governing bribery in the private sector as a form of corruption.